COMPLEX DI-HYDRATE CALCIUM PHOSPHATE - GLUTARALDEHYDE: FORMULATION MECHANISM - Mohammed, Bouzid; Amina, Djadi; Boudjemaa, Bezzazi (European Scientific Journal, ESJ, 2015)
The di-hydrate calcium phosphate CaHPO4, H2O (DCPD) reacts with glutaraldehyde OCH – (CH2)3 – CHO (GL) in an aqueous solution to give the complex OCH – (CH2)3 – CH(OH) – O – PO3Ca (DCPD-GL). In the solution, the complex appears in the form of hydrates (enolic stabilized by intramolecular isomery d, e, f and as the corresponding carboxylic acid g). In the solid state it is the enolic form wich dominates (cis and trans).